(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The flexibility of interaction between the movement of macroeconomic variables that affect and are affected by the balance of payments, especially the movement of the current account, implies a perception of the maturity of economic development and what the theory assumes from the launch of a wide range of economic movement that varies in the degree of its influence according to the level of economic development and the vitality of the internal/external overlap relations through the assumed response to the movement of the macroeconomic variables. On this basis, it is possible to estimate the soundness and rationality of the economic decision taken that takes into account the required reciprocal repercussions between the current account and the macroeconomic variables. The research concluded the validity of its hypothesis in the Iraqi economy , that the economy’s structural characteristics impede the achievement of the required reciprocal response between the current account situation and the movement of macroeconomic variables. The importance of this research in taking care of the analysis of the interrelationships between the Iraqi economy and the current account situation is an additional perspective in the analysis of the level of development and what an economic decision maker should take into account in his perception is to exceed the economic decision taken interms of possibility or inability to achieve the desired results of his decision This research is based on theoretical literature in macroeconomics and inter nationally to follow up and analyze internal L external interference relationships and following descriptive analysis and standard assessment of the inter relationships between the selected macroeconomic variables and the current account situation.